Arvind Thomas: Piers Plowman and the Reinvention of Church Law in the Late Middle Ages. Toronto: University of Toronto Press, 2019 - Pihl, Erika (Mirator, 2022)
A book review of Arvind Thomas: Piers Plowman and the Reinvention of Church Law in the Late Middle Ages. Toronto: University of Toronto Press, 2019